Psychiatric Assistance Dog Use for People Living With Mental Health Disorders - Lloyd, Janice; Johnston, Laura; Lewis, Julia (Frontiers in Veterinary Science, 2019)
A psychiatric assistance dog (PAD) is a service dog that is trained to assist its owner who has been diagnosed with a mental health condition such as PTSD, schizophrenia, depression, anxiety, or bipolar disorder. Little is known about PAD usage. Hence, owners registered with the charity ‘mindDog’ were invited to participate in an online survey to gain a better understanding of the person-dog team. 199 people completed the survey. Participants learned about PADs through the internet (37%), their health-care practitioner (32%) or family/friends (30%). The dogs in the sample were of varying age, gender and breed. The most common reasons for people to choose a dog to be a PAD were temperament (60%) and size/weight (48%). Just under half (48%) of the dogs had been acquired by the owner specifically to be trained as a PAD, and the rest were existing pets. All the dogs were trained by a combination of the owner and a qualified trainer; none were trained exclusively by assistance/service dog provider organizations. The median age of the participants at the time of data collection was 47 years, ranging from 10 to 75 years. Most (77%) identified as female. Depression (84%), anxiety (social 61%; generalized 60%), PTSD (62%) and panic attacks (57%) were the most self-reported mental health diagnoses. The most common tasks the dogs performed were: reduction of anxiety through tactile stimulation (94%); nudging/pawing to bring back to the present (71%); interrupting an undesirable behavioural state (51%); body contact (50%); deep pressure stimulation (45%) and blocking contact from other people (42%). PAD usage decreased (46%), increased (30%) or did not change (24%) participants’ use of psychiatric/other health-care services. This study show that owners have a variety of mental health diagnoses, and their dogs fulfil different tasks to support them in daily life. Every participant described the relationship with his/her PAD as positive, suggesting that a successful working partnership does not require the dog to have been bred/raised specifically for the role. A better understanding of the person-dog team may help inform the appropriate choice, training and use of PADs for people living with mental health problems.